The Politics of Decolonial Investigations - Mignolo, Walter (Book collections on Project MUSE., 2021)
"Walter D. Mignolo provides a sweeping examination of how colonialty has operated around the world in its myriad forms between the sixteenth and twenty-first centuries while calling for a decolonial politics that would delink from all forms of Western knowledge."--